An investigation of availability, accessibility and affordability of optometric services in the rural Mutale Municipality of Vhembe District, Limpopo Province, South Africa - Thivhafuni, Lufuno Godfrey (My University, 2011)
Refer to the document
Thesis (MPH.) -- University of Limpopo, 2011
Keywords: Optometric services; Eye care; Ophthalmology clinics; Eye, Diseases -- Health aspect; Optometry -- South Africa -- Limpopo